2019
DOI: 10.1101/777565
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Massively parallel CRISPRi assays reveal concealed thermodynamic determinants of dCas12a binding

Abstract: The versatility of CRISPR-Cas endonucleases as a tool for biomedical research has lead to diverse applications in gene editing, programmable transcriptional control, and nucleic acid detection. Most CRISPR-Cas systems, however, suffer from off-target effects and unpredictable non-specific binding that negatively impact their reliability and broader applicability. To better evaluate the impact of mismatches on DNA target recognition and binding, we develop a massively parallel CRISPR interference (CRISP… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 65 publications
0
10
0
Order By: Relevance
“…Here we use a 19-nt direct repeat as a Cas12a handle along with a 20-nt DNA targeting region (Figure 4B ). The F. novicida Cas12a uses a ‘TTV’ or ‘TTTV’ PAM ( 22 , 42 ), which targets the −35 box of the same σ 70 promoters in the dCas9 designs. We made our Cas12a crRNAs target these promoter regions on the template strand, with the idea that the dCas9 orthogonality with sgRNAs would carry over to the dCas12a system.…”
Section: Resultsmentioning
confidence: 99%
“…Here we use a 19-nt direct repeat as a Cas12a handle along with a 20-nt DNA targeting region (Figure 4B ). The F. novicida Cas12a uses a ‘TTV’ or ‘TTTV’ PAM ( 22 , 42 ), which targets the −35 box of the same σ 70 promoters in the dCas9 designs. We made our Cas12a crRNAs target these promoter regions on the template strand, with the idea that the dCas9 orthogonality with sgRNAs would carry over to the dCas12a system.…”
Section: Resultsmentioning
confidence: 99%
“…A single dCas CRISPRi inverter functions by driving the production of a gRNA which programs dCas to bind to and suppress expression from a targeted output promoter. 9 In our work, the inverter drives GFP production (Fig. 1A).…”
Section: Measuring Input and Output Leak Of A 1x Crispri Invertermentioning
confidence: 85%
“…It has been shown that synthetic transcription factors based on CRISPR interference (CRISPRi) [6][7][8][9][10] can be used to reprogram cellular function. A catalytically-dead CRISPR protein, designated dCas, can be utilized in bacteria as a programmable transcriptional repressor by blocking RNA polymerase transcription at the CRISPR binding site (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Based on large-scale editing or binding experiments undertaken in non-plant systems, CRISPR-Cas off-target edits can be largely mitigated by prioritizing target specificity during sgRNA design by ensuring that your target sequence is unique and does not occur elsewhere in the genome, either as an exact match or with a low level of mismatches (Kim et al 2016;Luo et al 2019;Specht et al 2020). Although this may be straightforward in species with small genomes, this may prove more challenging in species that have undergone whole-genome duplications.…”
Section: Off-target Editsmentioning
confidence: 99%